Early Carboniferous adakitic rocks in the area of the Tuwu deposit, eastern Tianshan, NW China: Slab melting and implications for porphyry copper mineralization. (1st May 2015) - Wang, Yin-Hong; Xue, Chun-Ji; Liu, Jia-Jun; Wang, Jian-Ping; Yang, Jun-Tao; Zhang, Fang-Fang; Zhao, Ze-Nan; Zhao, Yun-Jiang; Liu, Bin
Highlights: Tonalitic rocks occurred at ca.332 Ma, and the Cu mineralization formed during the same period. Tonalitic rocks show geochemical affinities similar to those of adakites. Tonalitic rocks were formed by interactions between subducted oceanic slab and mantle wedge peridotites. Tonalitic rocks resulted from the northward subduction of the paleo-Tianshan ocean plate. Abstract: Existing geochronological and geochemical data for the Early Carboniferous magmatic rocks in the eastern Tianshan, Xinjiang, have been interpreted in a variety of theories regarding petrogenesis and geodynamic setting. The proposed settings include rift, back-arc basin, passive continental margin, island arc, ridge subduction, and post-collisional environment. To evaluate these possibilities, we present new SHRIMP zircon U–Pb geochronology and geochemical data, whole-rock geochemical, Hf isotope, and S isotope data for tonalitic rocks and ores associated with the Tuwu porphyry copper deposit located in the center of the late Paleozoic Dananhu–Tousuquan arc, eastern Tianshan. SHRIMP zircon U–Pb dating indicates that the magmatic activity and thus associated copper mineralization occurred ca.332 Ma. The tonalitic rocks are calc-alkaline granites with A/CNK values ranging from 1.16 to 1.58; are enriched in K, Rb, Sr, and Ba; and are markedly depleted in Nb, Ta, Ti, and Th. They show geochemical affinities similar to adakites, with high Sr, Al2 O3, and Na2 O contents and La/Yb ratios; low Y and Yb contents; and slight positive Eu anomalies. In situ Hf isotopic analyses of zircons yielded positive initial ε Hf ( t ) values ranging from 6.9 to 17.2. The δ 34 S values of the ore sulfides range from −3.0‰ to +1.7‰, reflecting a deep sulfur source. Our results indicate that the paleo-Tianshan oceanic slab was being simultaneously subducted northward beneath the Dananhu–Tousuquan arc, and southward beneath the Aqishan–Yamansu arc during the Early Carboniferous. The Tuwu adakitic tonalitic rocks were derived from the partial melting of the subducted paleo-Tianshan oceanic slab, which was subsequently hybridized by mantle wedge peridotites. The slab-derived magmas have considerably high copper contents and are highly oxidized, thus leading to porphyry copper mineralization. Such Early Carboniferous tonalitic rocks that are widespread in the eastern Tianshan define a province with high potential for copper mineralization.